Economic evaluation of evidence-based strategies to reduce unhealthy alcohol use: a resource allocation guide - Hendrie, Delia; Miller, Ted R. (Frontiers in Public Health, 2025)
IntroductionIn the context of limited budgets to implement public health measures, cost-effectiveness is an important factor for policy makers to consider. Evidence from high-income countries on the outcomes and costs of interventions demonstrating success in reducing alcohol-related harm offers valuable guidance for resource allocation decisions in low- and middle-income settings.MethodsPublished reviews of interventions shown or likely to reduce alcohol-attributable harm were identified. Data on outcomes was extracted and standardized to allow consistent reporting of return on investment. Intervention costs were calculated using a ‘bottom-up’ approach based on quantity of resources and unit price. Benefit–cost ratios and incremental cost-effectiveness ratios were calculated for each intervention.ResultsAcross the various categories of alcohol harm reduction programs, interventions demonstrating good value for money were identified. These categories were availability of alcohol; marketing of alcoholic beverages; pricing policies; drink driving policies; workplace interventions; health sector programs; youth development programs; and school-based substance abuse prevention.ConclusionConsistent estimates of return on investment of alcohol harm reduction interventions provide an effective mechanism to filter out interventions of questionable value. Policymakers should also consider factors such as political feasibility, local priorities, cultural appropriateness, affordability, and the immediacy of impact when selecting a comprehensive package of strategies.